PENGARUH KNOWLEDGE MANAGEMENT BUMDES DAN LEADERSHIP KEPALA DESA TERHADAP PEREKONOMIAN DESA PASCA BENCANA TSUNAMI - Syamsudin, Syamsudin; Dasmaran, Verliani; Triyulaeli, Triyulaeli (COMPETITIVE, 2021)
The purpose of the study was to find out how the influence of BumDes Knowledge Management and Village Head Leadership on the village economy after the Tsunami Disaster. Research conducted using explanatory research, namely research that explains the causal relationship between the variables studied, the type of research is quantitative research. The unit of analysis used is the Teluk village community. The study population was 2,842 families (Data from the Teluk Village Office), the total sample of the study was 143 families. The data obtained is based on the sampling technique using the accidental sampling method, which is a technique of selecting respondents as a sample by chance but within the specified area, in this case the Teluk Village community, BUMDES employees and Teluk Village officials.